Global acute-on-chronic liver failure trends during 2012–2022: A bibliometric study - Cheng-zhi Bai; Juan Ren; Xue Zhang; Yi-yang Hu; Xiao-ping Wang; Xiao-wei Tang; Shan-hong Tang (Heliyon, 2024)
Introduction: Acute-on-chronic liver failure (ACLF) is a clinical syndrome with high short-term mortality. ACLF has been increasingly studied in recent years; however, a bibliometric analysis of the entire ACLF field has not been conducted. This study assesses current global trends and hotspots in ACLF research. Materials and methods: The core Web of Science database was searched for all ACLF-related publications conducted during 2012–2022. The data included information on the author, country, author keywords, publication year, citation frequency, and references. Microsoft Excel was used to collate the data and calculate percentages. VOSviewer software was used for citation and density visualization analysis. Histogram rendering was performed using GraphPad Prism Version 8.0 and R software was used to supplement the analysis. Result: A total of 1609 ACLF-related articles from 67 different countries were identified. China contributed the most literature, followed by the United States. However, Chinese literature only had the 4th highest number of citations, indicating that cooperation with other countries needs to be strengthened. The Journal of Hepatology had the highest number of ACLF-related citations. Prognosis was one of the most common author keywords, which may highlight current research hotspots. Bacterial infection was a common keyword and was closely related to prognosis. Conclusion: This bibliometric analysis suggests that future research hotspots will focus on the interplay among bacterial infection, organ failure, and prognosis.